FUNCTIONAL AND RADIOLOGICAL OUTCOME OF DIFFERENT PINNING CONFIGURATION (CROSS PINNING VERSUS DIVERGENT PINNING) IN FIXATION OF EXTRA-ARTICULAR FRACTURE OF DISTAL ENDRADIUS IN ELDERLY PATIENTS - SAIYAM, SHAILENDRA; UIKEY, KISHOR; BHALAVI, MONA; DAYA, MORIN JOY (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of the study is to compare the functional and radiological outcomes of different pinning configuration (cross pinning versus divergent pinning) in the fixation of extra-articular fracture of distal end radius in elderly patients. Methods: An observational prospective study was conducted at Sri Aurobindo Medical College and PG Institute, Indore, MP, from December 2019 to May 2021. After the approval of the Institutional Ethics Committee, informed consent was obtained from the 40 elderly patients of the both sex in the age group of more than 50 years with closed fracture. 20 Patients were subjected to divergent pinning and 20 patients were subjected to cross pinning. Regular follow-up with the X-ray imaging. Results: Statistically no significant difference was found in palmar tilt, radial shortening, and loss of radial deviation. Mayo wrist score compare between the two groups. The result showing the functional outcome of configuration B (cross-pinning) is better than that of configuration A (divergent pinning). The only significant complication is pin migration, pin site infection, and stiffness. Pin tract infections are resolved by oral antibiotics, good pin tract care and wrist stiffness treated with vigorous physiotherapy. Conclusion: Cross pinning had better functional and radiological outcome as compared to the divergent pinning in extra-articular fracture of the distal end of the radius. The percutaneous pinning technique is less time-consuming and allows earlier rehabilitation without jeopardizing the fracture alignment.